Lev Vygotsky: From Theator to Psychology (Revue internationale du CRIRES : innover dans la tradition de Vygotsky, 2017)
The article presents the analysis of L. S. Vygotsky’s works dedicated to the theater arts and is organized according Vygotsky’s di˙erent life and work stages. Meanwhile, special attention is paid to the Gomel period during which a large number of reviews were written by Vygotsky and publishe in “Nash ponedel’nik” and “Polesskaia pravda” newspapers. It is shown that even at the beginning of his work, he was interested not only in a range of problems in art, but also psychological problems related to art perception and creativeness. Vygotsky’s usage of structural concept ideas about the peculiar properties of literary text composition are also explored. Vygotsky analyzes the socio- psychological mechanisms of theatrical art e˙ect. Furthermore, those areas which are widely used by Vygotsky in determining the characteristics of cast reincarnation are examined. Special emphasis is placed on the di˙erent elements of the actor techniques (speech, movement, emotional expression, acting personality and etc.). Materials are widely used in this study and help identify the socio- cultural context that deﬁned Vygotsky’s values at di˙erent stages of his work, related to his drama criticism and his formation as a professional psychologist.
Keywords: L.S. Vygotsky; Theater arts; Drama criticism; Sociology of art; Theater as a social phenomenon; Levels of structural text analysis; Acting activity; Psychology of the actor reincarnation technology; Theater action logic; Psychotechnics; Sign-meaning-symbol